Hyperreality and the Epistemological Crisis of Contemporary Communication: A Philosophical Review of the Ethical Philosophy of the Islamic Broadcasting Ecosystem in the Post-Truth Era - Ikhwansyah Nasution; Rubino; Muhammad Randicha Hamandia; Zhila Jannati (Jurnal Administrasi Pemerintahan Desa, 2026)
The ontological and epistemological transformations which occurred in the digital media ecosystem have created a communication disruption which reduces objective truth to a hyperreality commodity through its philosophical assessment. The study seeks to dismantle post-truth communication ethics problems while building an Islamic broadcasting system according to ethical principles. The study employs library research methods to examine philosophical texts and communication ethics using a philosophical hermeneutic methodology. Current digital communication systems operate as simulacra because users cannot distinguish between actual existence and virtual creation which leads to an ethical void that follows algorithmic patterns and constant online connections. Islamic broadcasting which depends on the values of liberation and truth (al-haqq) encounters major difficulties when prophetic messages transform into public entertainment. The study presents a new framework for communication ethics which combines tabayyun epistemological knowledge with discourse ethics to counteract common information practices. Islamic communication ethics serve two purposes established through their role as moral behavior guidelines and their function as a system which helps individuals restore their dignity when they experience technological disconnection